Use of acupuncture in stroke and stroke complications: a systematic review and meta-analysis based on sham-controlled trials - Wang, Xiaoyu; Li, Jinquan; Yao, Kuan; Cheng, Zhiwen; Jiang, Tao; Liu, Wei; Li, Huan; Xiong, Bowen; Zhu, Hao; Zhang, Xiaofei; Song, Wenjing; Lu, Yuxin (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the efficacy of acupuncture in sham-controlled trials for stroke and its complications, compare the clinical differences between acupuncture groups and sham groups, and assess potential factors contributing to these differences.MethodsMedical Subject Headings searches of 7 databases were conducted from January 1, 2000, to December 31, 2024. The primary outcome was the Barthel Index (BI), and the secondary outcomes included the scores of the National Institute of Health Stroke Scale (NIHSS), Quality of Life Scale (QOL), Hamilton Depression Scale (HAMD), and adverse events. Meta-analysis systematically compared acupuncture with sham/placebo acupuncture, analyzing pooled data according to distinct quantitative acupuncture factors, with their corresponding 95% confidence intervals (CIs). Random-effects modeling was performed to pool the effect sizes. The quality of RCTs and evidence was evaluated by the Risk of Bias Tool and the Grading of Recommendations Assessment, Development, and Evaluation approach (GRADE), respectively.ResultsA total of 24 RCTs were included. The risk of bias was usually with some concerns. Compared with sham/placebo acupuncture, acupuncture significantly improved neurological function as measured by the NIHSS [7trails, n = 963; mean difference (MD) −1.10, 95%CI −1.94 to −0.26; GRADE low], enhanced quality of life assessed by the Stroke Specific Quality of Life scale(SSQOL) score (3trails, n = 756; MD 13.91, 95%CI 6.02 to 21.80; GRADE moderate), and reduced depressive symptoms according to the HAMD score(5trails, n = 361; SMD −0.54, 95%CI −1.11 to −0.03; GRADE low). However, there was no difference in the daily living ability measured by BI score (5trails, n = 454; MD 2.58, 95%CI 0.51 to 4.66; GRADE low). The variations in needling depth, type, manual manipulation, and de qi, could lead to significant differential effects.ConclusionThese findings suggest that acupuncture is associated with improved life quality, neurological function, and depressive symptoms in stroke patients, although it does not appear to enhance abilities of daily living. Future research should ascertain whether needling depth, type, manual manipulation, and de qi are correlated with optimal acupuncture strategies and sham-control design methodologies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023378930.